The Proposal of an Instructional Design Modelformaternity Nursing in Japan-Simulation-based Education for Improving Clinical Judgement (International Journal of Nursing Education, 2021)
Clinical judgement is a prerequisite for nurses for extending efficient health care based on theireducation, knowledge, reasoning, intuitive thinking and experience. Nurses involved in maternitynursingprovide care toexpectant and new mothers before, during and after child birth.Therefore, effectivenursing education plays a very important role in increasing the nurses’professional competencies andimproving the quality of care provided by them. However, the spread of COVID-19 in Japan and thechanging social conditions surrounding perinatal care have made it necessary to introduce simulationeducation to improve clinical judgement skills. In this paper, we propose an instructional design foreffective simulation education for maternity nursing as an alternative to practical training in a clinicalsetting. The design was developed based onMerrill’sfive principles of instruction.The high-fidelitysimulation task was constructed according tothecognitive load theory, controlling for three differentloads.We referred to Tanner’s clinical judgementmodel and discussed relevant references on ‘intuition’or ‘tacit knowledge’ as a component of clinical reasoning patterns.We also discussed the importance of‘intuition’ and debriefing on experiencesas per the Dreyfus model.Relevant papers were reviewed andscales developed to assess simulation-based education.